(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2015)
Ten chilli (Capsicum frutescens L.) genotypes were subjected to an experiment for analysis of stability and genotype-environment interaction in randomized complete block design with four environments using additive main effect and multiplicative interaction (AMMI) model. Parameters for experimentation were number of fruits per plant, fruit diameter, leaf area index, fruit length without panicle, number of seeds per fruit and individual plant fruit yield. A significant mean sum of square due to Genotype (G), Environment (E) and G × E interaction for all the characters was showed by combined ANOVA, suggested differential responses of genotypes in different environments. The AMMI biplots for yield indicated that, BD-2059 and Bogura Jatt were stable across the environments. Genotype Kalo Dhawna morich had positive interaction effect was better suited to favourable environment for most of the traits. According to AMMI characterisation, Env-2 was found highly favourable for better expression of the studied traits for all the genotypes.